The current status of old traditional medicine introduced from Persia to China - Shi, Jinmin; Yang, Yifan; Zhou, Xinxin; Zhao, Lijun; Li, Xiaohua; Yusuf, Abdullah; Hosseini, Mohaddeseh S. M. Z.; Sefidkon, Fatemeh; Hu, Xuebo (Frontiers in Pharmacology, 2022)
Traditional Chinese medicine (TCM) includes over ten thousand of herbal medicine, some of which were introduced from outside countries and territories. The Silk Road that enabled the exchange of merchandise such as teas, silks, carpets as and medicine between the East and West of the Eurasia continent. During this time, the ‘Compendium of Materia Medica’ (CMM) was composed by a traditional medicine practitioner, Shizhen Li (1518-1593) of the Ming Dynasty. This epoch-making masterpiece collected knowledge of traditional medical materials and treatments in China from the 16th century and before in utmost detail, including the origin where a material was obtained. Of 1892 medical materials from CMM, 46 were came from Persia (now Iran). In this study, the basic information of these 46 material, including the time of introduction, the medicinal value in TCM theory, together with the current status of these medicine in China and Iran, are summarized. It is found that 20 herbs and 4 stones out of the 46 materials are registered as medicinal materials in the latest China Pharmacopoeia. Now most of these herbs and stones are distributed in China or replacements are available but saffron, ferula, myrrh and Olibanum are still highly dependent on importing. This study may contribute to the further development, exchange and internationalization of traditional medicine of various background in the world, given the barriers of transportation and language are largely eased in nowadays.